P15. Multimodal mapping of nerve pathology with a multichannel approach. Issue 8 (August 2018) - Weitkamp, F.; Elzenheimer, E.; Schulte-Mattler, W.; Schmidt, G.; Laufs, H.
Abstract : Objective: Clinical electroneurography, the diagnostic standard for the assessment of thickly myelinated peripheral nerves, is of limited spatial resolution since it provides only average data (nerve conduction velocity [NCV], nerve or muscle action potential amplitude) on relatively large nerve segments. Accordingly, different distribution patterns of axonal or myelin pathologies cannot be distinguished. But precisely this is relevant to ensure correct diagnosis and therapies. These can pose a relevant burden on the patient ranging from spontaneous recovery over surgical to medical, partly highly expensive, treatment. Hence, our main objective is to optimize the diagnostic specificity via a multichannel neurographical approach. By adding ultrasound data, a functional-structural model can be developed as a novel basis for medical decision making. Methods: Based on ultrasound, eight electrodes are positioned along the course of the median and ulnar nerve, respectively, and nerve depth (distance to skin) profiles are recorded. Bipolar direct current stimulation is applied close to the M. abductor pollicis brevis and the M. abductor digiti minimi, resulting in the excitation of both motor and sensory nerve fibers (mixed nerve technique) (Buschbacher, 1999 ) such that eight mixed nerve action potentials (NAPs) can be recorded along the nerve. We performed reference measurements in 10 healthy volunteers. Results: Median nerve depth ranged from 2 to 23 mm, and we recorded reproducible signals at all locations with a maximum of 8 averages (at 20 mm) in good correspondence with previously published values (Fig. 1 ) (Watson et al., 2002 ).Fig. 2 reports the (inverse) relationship between NAP amplitudes and depth. Discussion: Using the setup described, we reliably obtain NAP and their latencies of two peripheral nerves along their course with slight or no averaging. The interesting question is, if and how different pathologies influence the amplitude level. The next step will be the assessment of nerve pathologies to test that diagnostic and therapeutic decision making benefits from structural-functional nerve mapping with high spatial resolution.